European financial integration and corporate governance - Claudia M. Buch; Ralph P. Heinrich (Deutsche Bank Research, 2002)
The paper studies the link between the integration of European financial markets and corporate governance in Europe. The focus of the paper is on how integration affects the interplay of ownership structures, capital structures, and monitoring, all of which can be used to govern agency problems at the firm level. Integration is a process which comprises the abolition of capital controls, the harmonization of institutions, and the creation of a common currency area. These elements, in turn, affect the liquidity of markets, the cost of monitoring, and the cost of debt. Based on these considerations, implications for changes in the structure of corporate governance systems are derived.
Keywords: G30; D23; 330; corporate governance; complementarity; financial integration; Finanzmarkt; Marktintegration; Internationaler Finanzmarkt; Corporate Governance; Kapitalstruktur; Eigentümerstruktur; EU-Staaten